2015 Moratuwa Engineering Research Conference (MERCon) 2015
DOI: 10.1109/mercon.2015.7112342
|View full text |Cite
|
Sign up to set email alerts
|

A techno-economic analysis for an integrated solar PV/T system with thermal and electrical storage — Case study

Abstract: A hybrid photovoltaic/thermal (PV/T) system is having the capability to convert solar energy to both electricity and thermal energy simultaneously and these systems can use to accomplish the energy demand of buildings. Performance analysis of such systems becomes essential to design PV/T systems matching with the operating conditions. It is essential to extend the energy flow analysis used in this regard considering economic limitations especially for urban applications. In this study a practical method to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…It has been found that most of the EU28 member states have good conditions for district heating [50]. Hybrid photovoltaic-thermal systems are also interesting, because they have the ability to convert solar energy into electricity and into thermal energy simultaneously [51] and can be used to meet, to a large extent, the energy demand of hospitals [52]. Another interesting option is to use solar energy to produce cold by means of absorption equipment [53].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that most of the EU28 member states have good conditions for district heating [50]. Hybrid photovoltaic-thermal systems are also interesting, because they have the ability to convert solar energy into electricity and into thermal energy simultaneously [51] and can be used to meet, to a large extent, the energy demand of hospitals [52]. Another interesting option is to use solar energy to produce cold by means of absorption equipment [53].…”
Section: Discussionmentioning
confidence: 99%
“…As explained in [15,16], solar energy can be converted to both electricity and thermal energy simultaneously by a hybrid photovoltaic/thermal (PV/T) system which can also maintain the energy demand of buildings. While designing PV/T systems to match with the operating conditions, performance analysis of such systems is important.…”
Section: Enabling Technologies and Applicationsmentioning
confidence: 99%
“…Furthermore, solar and battery technologies are often installed at individual building scale, and it could be interesting to look at such installation at neighbourhood scale [18]. This will clearly improve the potential of solar panels to be part of an integrated energy system [19].…”
Section: Introductionmentioning
confidence: 99%